2015
DOI: 10.1038/srep07888
|View full text |Cite
|
Sign up to set email alerts
|

Large number of putative chemoreception and pheromone biosynthesis genes revealed by analyzing transcriptome from ovipositor-pheromone glands of Chilo suppressalis

Abstract: The chemoreception role of moth ovipositor has long been suggested, but its molecular mechanism is mostly unknown. By transcriptomic analysis of the female ovipositor-pheromone glands (OV-PG) of Chilo suppressalis, we obtained 31 putative chemoreception genes (9 OBPs, 10 CSPs, 2 ORs, 1 SNMP, 8 CXEs and 1 AOX), in addition to 32 genes related to sex pheromone biosynthesis (1 FAS, 6 Dess, 10 FARs, 2 ACOs, 1 ACC, 4 FATPs, 3 ACBPs and 5 ELOs). Tissue expression profiles further revealed that CsupCSP2 and CsupCSP10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 57 publications
4
51
0
Order By: Relevance
“…The latter authors proposed that CSPs in the pheromone glands might act by solubilising hydrophobic pheromones produced by the glands and releasing them into the environment. Transcriptome projects have identified genes encoding CSPs in the pheromone glands of the lepidopteran Spodoptera litura (Zhang et al., ), Chilo suppressalis (Xia et al., ), Agrotis ipsilon (Gu et al., ), Agrotis segetum (Strandh, Johansson & Löfstedt, ) and Sesamia inferens (Zhang et al., ). The number of such reports is increasing rapidly with examples from different orders of insects.…”
Section: Multiple Functions Of Obps and Cspsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter authors proposed that CSPs in the pheromone glands might act by solubilising hydrophobic pheromones produced by the glands and releasing them into the environment. Transcriptome projects have identified genes encoding CSPs in the pheromone glands of the lepidopteran Spodoptera litura (Zhang et al., ), Chilo suppressalis (Xia et al., ), Agrotis ipsilon (Gu et al., ), Agrotis segetum (Strandh, Johansson & Löfstedt, ) and Sesamia inferens (Zhang et al., ). The number of such reports is increasing rapidly with examples from different orders of insects.…”
Section: Multiple Functions Of Obps and Cspsmentioning
confidence: 99%
“…In most cases, the role of the binding proteins has been demonstrated or suggested to be that of a carrier for semiochemicals, hormones or other biologically active chemicals. Numbers refer to species studied and references, as follows: (1) S podoptera litura (Zhang et al., ); C hilo suppressalis (Xia et al., ); A grotis ipsilon (Gu et al., ); A grotis segetum (Strandh et al., ); S esamia inferens (Zhang et al., ); B ombyx mori (Dani et al., ); (2) A pis mellifera (Iovinella et al., ); (3) L eptopilina heterotoma (Heavner et al., ); P teromalus puparum (Wang et al., ); S irex noctilio (Wang et al., ); A pis mellifera (Li et al., ) (4) D rosophila melanogaster (Dyanov & Dzitoeva, ; Takemori & Yamamoto, ); (5) H elicoverpa armigera (Y.L. Sun et al., 2012 b ); (6) L ocusta migratoria (Ban et al., ; Zhou et al., ); (7) A edes aegypti (Li et al., ; Sirot et al., ); (8) A pis mellifera (Baer et al., ); (9) T ribolium castaneum (Xu et al., ); (10) P eriplaneta americana (Nomura et al., ; Kitabayashi et al., ); (11) A pis mellifera (Maleszka et al., ); (12) S olenopsis invicta (Cheng et al., ); (13) L ocusta migratoria (Guo et al., ); (14) A edes aegypti (Calvo et al., ); A nopheles stephensi (Isawa et al., ); (15) P hormia regina (Ishida et al., ); (16) M amestra brassicae (Nagnan‐Le Meillour et al., ); H elicoverpa armigera (Y.L.…”
Section: Multiple Functions Of Obps and Cspsmentioning
confidence: 99%
“…In recent years, several studies have reported expression of genes encoding olfactory receptors not only on the antennae and maxillary palps but also in ovipositors of a variety of lepidopteran species, yet their function remains largely unknown. For example, in the noctuid Sesamia nonagrioides, Glaser et al reported expression of both IRs and ORs, as well as ORCo (Glaser et al, 2013); in pheromone glands and ovipositor of the grass moth Chilo suppressalis, expression of two ORs but no ORCo has been described (Xia et al, 2015). Finally, in Heliothis virescens two pheromone receptors are expressed in the ovipositor as well, where they might be involved in feedback regulation of the pheromone release (Widmayer et al, 2009), but again their function has not been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that CvesOBP2 can bind the Carpomya vesuviana male-emitted odor (Z)-3-hexen-1-ol acetate . Notably, most OBPs are expressed in antennae, which indicating the important functions of OBPs in antennal identification processes, such as in C. kiangsu (Li, Jiang & Dong, 2018), H. assulta (Jin et al, 2015) and C. suppressalis (Xia et al, 2015). AlinOBP11 is expressed in the tarsal gustatory sensilla of Adelphocoris lineolatus (Sun et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble OBPs have a conserved pattern of six cysteines that form three disulfide bridges (Leal, Nikonova & Peng, 1999). Pheromone binding proteins (PBPs) are members of a subfamily of OBPs (Zhou, 2010) that bind to pheromone compounds, participate in the pheromone recognition process and exhibit biased expression in antenna, such as in Eogystia hippophaecolus, Sesamia nonagrioides and Helicoverpa assulta (Glaser et al, 2013;Hu et al, 2016a;Li et al, 2015). CSPs have only four cysteines are smaller than OBPs (Pelosi et al, 2006), and bind to various odors (Ban et al, 2002;Briand et al, 2010;Jacquinjoly et al, 2001;Lartigue et al, 2002).…”
Section: Introductionmentioning
confidence: 99%